2010
DOI: 10.1016/j.polsoc.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The media's role in shaping Canadian civic and political engagement

Abstract: How does mediatised information affect attitudes and engagement in the civic/political spheres? The question is an important one, not only because of changing media forms but also because of the important role of the media in providing political information. As such, its intermediary role in shaping both political interest and political knowledge is heightened, both of which are important determinants of political engagement. This work uses the data from the 2003 General Social Survey to assess and compare var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Socialization for citizenship in adolescence can be influenced by parents, peers, schools and media (McLeod 2000). Among these sources, the media is currently one of the most influential socializing agents for adolescents, and it plays an important role in affecting civic engagement (O'Neil 2009).…”
Section: Civic Engagement and Social Networking Sitesmentioning
confidence: 99%
“…Socialization for citizenship in adolescence can be influenced by parents, peers, schools and media (McLeod 2000). Among these sources, the media is currently one of the most influential socializing agents for adolescents, and it plays an important role in affecting civic engagement (O'Neil 2009).…”
Section: Civic Engagement and Social Networking Sitesmentioning
confidence: 99%
“…At the same time, higher psychological 2 Y.P. Hsieh and M.-H. Li engagement in politics may also motivate users to search for and retrieve information online for civic and political affairs (Bimber, 2001(Bimber, , 2003O'Neill, 2010;Xenos & Moy, 2007). For example, by examining the data from the 2000 American National Election Studies (ANES), Bimber (2003) reported that citizens who have higher political efficacy and have used the Internet for political information were more likely to vote.…”
Section: Icts As Information Sources For Political Informationmentioning
confidence: 99%
“…Conversely, there is an alternative explanation that states that the process of political communication is a “virtuous circle” in which the attention to news media gradually reinforces civic engagement, just as civic engagement strengthens attention to news (Norris, 2000). Indeed, the type of media that are consumed may have differential effects on civic activity or political knowledge (Hooghe, 2002; Jeffres, Dobos, & Lee, 1988; Keum, Devanathan, Deshpande, Nelson, & Shah, 2004; O’Neill, 2009; Prior, 2003; Shah, 1998), but they do enhance civic engagement. Furthermore, the American public may be underinformed rather than uninformed, as the public consists mostly of information generalists rather than information specialists (Delli Carpini & Keeter, 2002).…”
Section: News Democracy and Civic Engagementmentioning
confidence: 99%